Surveillance programme of cirrhotic patients for early diagnosis and treatment of hepatocellular carcinoma: a cost effectiveness analysis. Issue 2 (1st February 2001) - Bolondi, L; Sofia, S; Siringo, S; Gaiani, S; Casali, A; Zironi, G; Piscaglia, F; Gramantieri, L; Zanetti, M; Sherman, M
Abstract : BACKGROUND: Hepatocellular carcinoma (HCC) is a major cause of death in cirrhotic patients. This neoplasm is associated with liver cirrhosis (LC) in more than 90% of cases. Early diagnosis and treatment of HCC are expected to improve survival of patients. AIMS: To assess the cost effectiveness of a surveillance programme of patients with LC for the early diagnosis and treatment of HCC. PATIENTS: A cohort of 313 Italian patients with LC were enrolled in the surveillance programme between March 1989 and November 1991. In the same period, 104 consecutive patients with incidentally detected HCC were referred to our centre and served as a control group. METHODS: Surveillance was based on ultrasonography (US) and α fetoprotein (AFP) determinations repeated at six month intervals. Risk factors for HCC were assessed by multivariate analysis (Cox model). Outcome measures analysed were: (1) number and size of tumours; (2) eligibility for treatment; and (3) survival of patients. Economic issues were: (1) overall cost of surveillance programme; (2) cost per treatable HCC; and (3) cost per year of life saved (if any). Costs were assessed according to charges for procedures at our university hospital. RESULTS: Surveillance lasted a mean of 56 (31) months (range 6–100). During the follow up, 61 patients (19.5%) developed HCC (unifocal at US in 49 cases), with an incidence of 4.1% per year of follow up. AFP, Child-Pugh classes B and C, and male sex were detected as independent risk factors for developing HCC. Only 42 (68.9%) of 61 liver tumours were treated by surgical resection, orthotopic liver transplantation, or local therapy. The cumulative survival rate of the 61 patients with liver tumours detected in the surveillance programme was significantly longer than that of controls (p=0.02) and multivariate analysis showed an association between surveillance and survival. The overall cost of the surveillance programme was US753 226, the cost per treatable HCC was US17 934, and the cost for year of life saved was US112 993. CONCLUSION: Our surveillance policy of patients with LC requires a large number of resources and offers little benefit in terms of patient survival. The decision whether to adopt a surveillance policy towards HCC should rely on the prevalence of the disease in the population and on the resources of a particular country.